2020
DOI: 10.1042/bsr20191445
|View full text |Cite
|
Sign up to set email alerts
|

Eupatilin alleviates airway remodeling via regulating phenotype plasticity of airway smooth muscle cells

Abstract: Childhood asthma is a common chronic airway disease, and its severe form remains a challenge. Eupatilin is a bioactive natural flavone that has been found to possess potential anti-asthma activity. However, the roles of eupatilin in asthma remain to be elucidated. In the present study, airway smooth muscle cells (ASMCs) were applied for the in vitro investigation since their phenotype plasticity make great contribution to airway remodeling during asthma pathogenesis. Our results showed that eupatilin suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…24 Besides, by inhibiting STAT3, Eupatilin attenuates airway remodeling and inhibits gastric cancer cell growth. 25,26 A recent study has shown that Eupatilin is associated with coagulation. It can inhibit arachidonic acid (AA)-induced platelet aggregation and thromboxane A2 (TXA2) and 5-hydroxytryptophan (5-HT) generation.…”
Section: Introductionmentioning
confidence: 99%
“…24 Besides, by inhibiting STAT3, Eupatilin attenuates airway remodeling and inhibits gastric cancer cell growth. 25,26 A recent study has shown that Eupatilin is associated with coagulation. It can inhibit arachidonic acid (AA)-induced platelet aggregation and thromboxane A2 (TXA2) and 5-hydroxytryptophan (5-HT) generation.…”
Section: Introductionmentioning
confidence: 99%
“…The review also presents the anti-inflammatory properties of eupatilin against various disease models and its molecular targets, antioxidant activity through different molecular mechanisms, and neuroprotective activity both in vitro and in vivo. In 2020, Li et al [ 200 ] conducted an in vitro experiment that showed that compound 89 suppressed the proliferation and migration of airway smooth muscle cells (ASMCs). Exposure of ASMCs to eupatilin increased the expression of contractile markers smooth muscle, whereas the expression of extracellular matrix (ECM) proteins, type I collagen (Coll I), and fibronectin were reduced; the activation of nuclear factor κB (NF-κB), signal transducer and activator of transcription 3 (STAT3), and AKT pathways caused by TGF-β1 in ASMCs was present.…”
Section: Biological Activitymentioning
confidence: 99%
“… 7 , 8 , 9 , 10 , 11 The main cellular components of the airway are the airway epithelial cells and the airway smooth muscle cells (ASMCs). 12 Studies have shown that one of the main reasons for airway remodeling in patients with asthma is an increase in the proliferation and migration of ASMCs. 13 , 14 Several inflammatory mediators are essential for airway remodeling.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Recent research has revealed that lncRNAs play a key role in airway remodeling and regulation of the proliferation and migration of ASMCs. 12 , 21 For example, lncRNA brain cytoplasmic RNA 1 (BCYRN1) promotes ASMCs proliferation and migration through the upregulation of receptor potential 1. 25 LncRNA antisense noncoding RNAs at the INK4 locus (ANRIL) have been reported to play a significant role in cancers and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation